Implantación de un sistema de contabilidad en la “Agroveterinaria Jessica”, ubicada en el Cantón Cascales, provincia de Sucumbíos, período correspondiente desde el 01 de enero al 31 de diciembre del 2016 - Cerón Bravo, Adriana Katherine (2018)
This research was developed in compliance with what determines the Academic Regime of the National University of Loja, prior to choosing the Degree of Engineering in Accounting and Auditing, and at the same time was developed with the purpose of knowing the economic situation of the Agroveterinary. Complying with the objectives in the thesis project, the documentation for the respective record was collected, then the Plan and Manual of Accounts was carried out according to the needs of the business, the Initial Inventory was also executed, in the that the Asset and Liability was defined, making known the Patrimony that the business has, also the register was created in the Daily Book, in which each one of the economic movements carried out in the period January-December is reflected, to be later increased and recorded in the Balance of Verification, data that served for the preparation of Financial Statements, which show the economic and financial reality of the business. Concluded with the exercise, the economic situation of the company was determined through the Statement of Financial Position, Income Statement and Statement of Cash Flow, providing a representative profit margin for its owner, as a priority it is recommended to continue applying this accounting process and make the most of available resources.